Experiências e percepções de indivíduos com dor no ombro após um tratamento com telerreabilitação: um estudo qualitativo - Luiz, Gustavo Rossi (Universidade Federal de São Carlos, 2024)
Introduction: The high incidence of shoulder pain in the general population, together with the challenges encountered in the public health system, reinforce the need for effective alternatives to meet the high demand of individuals with shoulder pain. The use of telerehabilitation for the treatment of musculoskeletal disorders has the potential to reduce costs and improve access for the population when compared to face-to-face treatment. Objective: To identify the experiences and perceptions of individuals with shoulder pain after a telerehabilitation treatment. Methods: This is a qualitative study using thematic analysis. Individuals aged between 18 and 60 who had completed a 12-week treatment consisting of therapeutic exercises and conducted by telerehabilitation were invited to take part in a semi-structured interview used as a data collection instrument. The interviews took place in person and were conducted by a single evaluator. The questions covered different aspects of the experience of the individuals who underwent the treatment and were drawn up together with the members of the research group. The interviews were recorded using a voice recorder and were carried out until the data was saturated. The transcription of the data, the extraction of relevant reports and the formulation of themes were carried out by two researchers independently, and there was discussion with a third researcher in the event of conflicting opinions. Results: Seven participants were interviewed (34.8 ± 15.3 years; 3 women and 4 men) and six main themes were obtained: (1) “facilitators of adherence to treatment”, (2) “possible barriers to adherence to treatment”, (3) “preference for the form of treatment”, (4) “progression of exercises”, (5) “continuity of treatment and satisfaction”, and (6) “confidence and motivation when participating”. The participants reported as facilitators that telerehabilitation is easy to integrate into their daily routines, the instructions provided by the research team were easy to understand and the support of the physiotherapist was helpful. However, the main barriers were the difficulty of maintaining adherence to the intervention and the perception that the intervention was monotonous. Participants initially reported a preference for face-to-face treatments before the intervention began, but this preference changed after undergoing the telerehabilitation intervention. Most participants faced no difficulties in managing the progression of their exercises during the intervention. In general, participants were satisfied with telerehabilitation and continued exercising at home after the intervention ended. Although initially unsure, participants gained confidence over the course of the intervention, citing pain relief and achieving the desired results as the main motivators. Conclusion: Overall, the participants interviewed reported positive experiences and perceptions of treatment with telerehabilitation for shoulder pain. From the reports, it was possible to understand the individuals' views and which factors favor the success of treatment with telerehabilitation for shoulder pain. The information obtained can help clinicians understand which patients may benefit most from one or other form of intervention among those addressed by the primary study. These findings can help physiotherapists inform patients about possible barriers and facilitators, improving shared clinical decision-making when choosing between telerehabilitation and face-to-face treatment.
Experiences and perceptions of individuals with shoulder pain after telerehabilitation treatment: a qualitative study
Keywords: Fisioterapia; Desordens musculares; OUTROS